Animal power unit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The one horse-power machine shown in the picture was constructed with hand tools by staff and students of the Development Technology Unit of Warwick University, I UK. It consists of easily-worked mild steel and wood. The University researchers,...